Tourism in the European Union - Rita, P. (2000)
Discusses the importance of tourism as the largest generator of wealth and employment in the world and the fact that, despite the clear evidence of tourism importance in economic and social terms and its undeniable perspectives of growth along the next two decades, it has registered great difficulties in obtaining its legal political recognition within the European Union. In conclusion, it is suggested that there ought to be a political recognition of the European tourism as one of the activities of the future, with an enormous capacity to provide new opportunities to satisfy important political objectives, such as the economic growth and wellbeing of populations, employment, regional development, and patrimonial value.